Seduction and repetition in Ovid's Ars amatoria 2 - Sharrock, Alison 1963- (Clarendon Press, 1994)
The Ars Amatoria is a poem about sex and poetry, and poetry as sex. Witty and subversive, it is a poem of seduction about seduction: the seduction of the 'implied' reader being initiated into the art of love, and ourselves, as we are seduced by the poet into the act of reading the poem